M. Walker. Branching Is Not a Bug; It’s a Feature: Personal Identity and Legal (and Moral) Responsibility / trans. from Engl. V. A. Pilipenko - V. A. Pilipenko (Омский научный вестник: Серия "Общество. История. Современность")
Prospective developments in computer and nanotechnology suggest that there is some possibility – perhaps as early as this century — that we will have the technological means to attempt to duplicate people. For example, it has been speculated that the psychology of individuals might be emulated on a computer platform to create a personality duplicate — an ‘upload’. Physical duplicates might be created by advanced nanobots tasked with creating molecule-for-molecule copies of individuals. Such possibilities are discussed in the philosophical literature as (putative) cases of ‘fission’: one person ‘splitting’ into two. Many philosophers, perhaps most, reject the idea of fission, appealing to some form of a ‘no-branching’ condition to rule out such possibilities. I argue, to the contrary, that there are good moral reasons to think that any account of personal identity that does not permit fission is deeply problematic, especially in connection with theorizing about criminal punishment. I discuss and reject David Lewis’ famous account of personal identity that invokes ‘multiple occupancy’ to allow for branching. In contrast, I offer an account of personal identity that permits branching using the type/token distinction to help with such puzzling cases.